Prosedur Pengelolaan Surat Masuk di Kantor Pos Medan Provinsi Sumatra Utara - Kristina Natalia Situmorang; Taruli Hutajulu; E M. Rivaldo Sinukaban; Renita Br Saragih (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to determine the description of the incoming mail management procedure in the General and Personnel section at the post office. The type of research used is descriptive qualitative, namely the author describes the results of observations, interviews, documentation and analyzes data obtained in the field. The results of the study indicate that the process of managing incoming mail in the general and personnel section, namely incoming mail starts from receiving letters, directing letters, delivering incoming letters, processing letters, storing letters. The letter management procedure at the post office runs optimally.